2015
DOI: 10.3389/fpls.2015.00361
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response to drought stress in Camptotheca acuminata seedlings from two provenances

Abstract: Drought stress is a key environmental factor limiting the growth and productivity of plants. The purpose of this study was to investigate the physiological responses of Camptotheca acuminata (C. acuminata) to different drought stresses and compare the drought tolerance between the provenances Kunming (KM) and Nanchang (NC), which are naturally distributed in different rainfall zones with annual rainfalls of 1000–1100 mm and 1600–1700 mm, respectively. We determined relative water content (RWC), chlorophyll con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 36 publications
(39 reference statements)
4
38
0
Order By: Relevance
“…Chlorophyll, a photosynthetic pigment, is involved in light absorption and plays an important role in plant photosynthesis. As drought stress can accelerate chlorophyll decomposition, chlorophyll content has been reported as the most frequently used metrics for ascertaining the severity of drought stress (Efeoğlu et al 2009;Ying et al 2015). As expected, we observed that the chlorophyll content in DA1 plants significantly decreased under S1 (Figure 2E).…”
Section: Chlorophyll Carotenoid and Proline Content Under Drought Asupporting
confidence: 83%
“…Chlorophyll, a photosynthetic pigment, is involved in light absorption and plays an important role in plant photosynthesis. As drought stress can accelerate chlorophyll decomposition, chlorophyll content has been reported as the most frequently used metrics for ascertaining the severity of drought stress (Efeoğlu et al 2009;Ying et al 2015). As expected, we observed that the chlorophyll content in DA1 plants significantly decreased under S1 (Figure 2E).…”
Section: Chlorophyll Carotenoid and Proline Content Under Drought Asupporting
confidence: 83%
“…D). WUE is an important physiological indicator for evaluatiing the adaption to water deficit, and plants with high WUE usually have a characteristic of strong drought tolerance (Steven , Schittenhelm and Schroetter , Ying et al ). The WUE increased in response to drought stress in both poplar species, but P. simonii showed higher WUE than P. deltoides cv.…”
Section: Discussionmentioning
confidence: 99%
“…Plants respond and adapt to drought stress through the induction of various morphological and physiological responses [64,65]. Many physiological factors may be involved in drought stress injury [66]. Drought stress can damage the photosynthetic apparatus and decrease leaf chlorophyll content [14], as well as transpiration rate, water content, and leaf angle [15].…”
Section: Discussionmentioning
confidence: 99%